DIGITIZATION AND CULTURE (CASE STUDY ON LOCAL WISDOM-BASED CULTURE DEVELOPMENT THROUGH NEW MEDIA BY SAGANG FOUNDATION) - Fitria Mayasari (Universitas Muhammadiyah Jakarta, 2019)
The presence of media plays a very important role to the growth and development of a culture, one of which is local culture. New media offers a variety of advantages compared to traditional media, such as users ability to adjust time. The demasification of new media also affects to the results and potential of the use of new media. Because the flow of information that takes place becomes more personal. Existing findings dissected the key ele- ment of successful in using new media as a strategy for political communication, campaigns and social movements. However, these efforts to use successful new media are often adhered by communities or institutions in large cities with adequate infrastructure and management. Therefore, it is interesting to see and analyze the use of new media in the field of cultural development from a non-profit organization. This study uses a case study approach to look at the strategy of developing local wisdom-based culture through new media conducted by the Sagang Foundation. Regarding the results of research and analysis, it is known that the characteristics of individuals, organizations, and the environment contribute to the results of the use of the media carried out by the Sagang Foundation. These characteristics successfully enhanced to the strategic results for organization in utilizing new media.Keywords: Digitization, Cultural, New Media, Sagang Foundation